The Analysis of Dietary Fiber Content and Preference Test on Cookies Substituted with Purple Sweet Potato Flour and Sorghum Flour - Elvia Eka Maheswari Kurnia; Mar'atus Solichah; Faurina Risca Fauzia (International Journal Labs, 2025)
Fiber consumption in Indonesia remains critically low, averaging only 10.5 grams per day, far below the recommended 25 grams daily intake. This study aimed to analyze the dietary fiber content and consumer preference of cookies substituted with purple sweet potato flour and sorghum flour to develop functional foods that could address this nutritional deficiency. An experimental design was employed utilizing four formulations: F0 (control) and F1–F3 (varying substitution ratios of purple sweet potato and sorghum flours). Twenty-five trained panelists conducted hedonic evaluation to assess sensory acceptability across color, taste, texture, and aroma parameters. Laboratory analysis determined the fiber content of each formulation. Fiber content increased progressively with higher substitution levels, with F3 containing the highest fiber concentration at 8.4%. Hedonic testing revealed no significant differences in color, taste, or texture preferences (p>0.05); however, aroma showed significant differences (p<0.05), with F0 being most preferred. Overall acceptability analysis identified F2 (containing 7% fiber, equivalent to 0.77g per piece) as the most accepted formulation, successfully balancing sensory appeal with nutritional enhancement. The findings demonstrate that purple sweet potato and sorghum flours can effectively increase dietary fiber in cookies without substantially compromising consumer acceptability, supporting their potential use in functional food development to address Indonesia's fiber deficiency crisis.